Terahertz conductivity mapping of thin films on smart textiles - Alexander Jäckel; Maximilian L. Hupfer; Enrique Castro-Camus; Daniel M. Mittleman; Gabriele Schmidl; Annett Gawlik; Jonathan Plentz; Martin Koch (Scientific Reports)
Abstract Smart textiles that promise to become sensors and actuators for multiple applications are an active area of research. Conductive textiles formed by coating a fabric with a conductive film will play a key role in such applications. Here we present contactless mapping of the terahertz (THz) conductivity of thin conductive films deposited on textiles. These conductivity maps enable non-destructive assessment of the conductivity of such layers and therefore the identification and localization of non-uniformities in local conductivity. The THz measurements are quantitatively consistent with four-point probe measurements of the same areas.